The development of musical projects within the framework of research + creation.: Methodological reflections on the project “From the ephemeral memory, to the ephemeral in memory. Interpretation of the works for cello and piano by the colombian composer Blas Emilio Atehortúa Amaya” (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2022)
The main purpose of this article is to present the reflections derived from the realization of the project “From the ephemeral memory to the ephemeral in memory. Interpretation of the works for cello and piano by the Colombian composer Blas Emilio Atehortúa Amaya”. In the first place, a brief contextualization of the subject will be presented based on what was raised by the Ministry of Science, Technology and Innovation of Colombia (Minciencias). Subsequently, the methodological process that led to the creation of an ephemeral work based on the interpretation of the four works for cello and piano by the composer will be describe. This retrospective will be complemented with the contributions from various authors in the disciplines of ethnography and ethnomusicology that will allow us to reflect on the conceptualization of the artistic practice.
Keywords: Research + Creation; Methodology; Works for Cello and Piano; Blas Emilio Atehortúa Amaya